FORECASTING DRUG SALES AFTER THE COVID-19 PANDEMIC IN PT. GRATIA HUSADA FARMA USING ARIMA METHOD - Airlangga, Radithya; Ineke Pakereng, Magdalena A. (Sean Institute, 2022)
Forecasting is the initial stage in production planning and serves as a foundation for subsequent production activities. The advent of the Covid-19 pandemic in Indonesia began in 2020, causing unstable sales. The ARIMA or Autoregressive Integrated Moving Average method is a medium-term forecasting method that generates relatively good prediction values compared to other methods. PT Gratia Husada Farma is a company active in the pharmaceutical field in Central Java. The sales data possessed by PT GHF is not yet optimally utilized and only serves as historical records. Through the obtained data, a sales forecasting analysis is conducted using the ARIMA method with parameters p, d, q of 1, 0, 1. Evaluation of the method using the RMSE formula results in a value of 2.229 (0.02229). This shows that the ARIMA method analysis has an acceptable error value, less than one of the critical values or alpha of 0.05.